Efficacy and Safety of Full-endoscopic Decompression via Interlaminar Approach for Central or Lateral Recess Spinal Stenosis of the Lumbar Spine: A Meta-analysis. Issue 24 (15th December 2018) - Lee, Chang-Hyun; Choi, Miyoung; Ryu, Dal Sung; Choi, Il; Kim, Chi Heon; Kim, Hyeun Sung; Sohn, Moon-Jun
Abstract : Study Design: A meta-analysis of five retrospective cohort studies. Objective: The aim of the study was to delineate the efficacy and safety of full-endoscopic decompression via the interlaminar approach for central or lateral recess spinal stenosis of the lumbar spine using a meta-analysis. Summary of Background Data: The paradigm of spinal endoscopy is shifting from treatment of soft disc herniation to that of lumbar spinal stenosis. Technical advancements have enabled full-endoscopic decompression in spinal stenosis surgery. There is few strong evidence supporting this surgical technique, and clinicians usually rely on their own opinions and experiences. Methods: A systematic search of electronic databases, including PubMed, EMBASE, Cochrane Library, Web of science, and KoreaMed, up to August 2017 was performed to identify studies concerning full-endoscopic decompression via the interlaminar approach for lumbar spinal stenosis. Changes in clinical outcomes [Oswestry Disability Index (ODI) and Visual Analog Scales (VAS) for back and leg pain] were compared with the minimal clinically important difference (MCID) for each item. We then calculated the mean differences and 95% confidence intervals (95% CIs) using random-effects models. Results: We included data from five studies involving 156 patients at 6- and 12-month follow-ups. The majority of enrolled papers included patients with neurogenic claudication due to central stenosis refractory to conservative management and excluded patients with significant instability or previous surgery. The overall mean difference of patients with ODI and VAS scores for leg and back pain exceeded the criteria for MCID. ODI scores improved by 41.71 (95% CI, 39.80–43.62) after the surgery, which was twice the MCID. The VAS leg and back pain scores improved by 5.95 (95% CI, 5.70–6.21) and 4.22 (95% CI, 3.88–4.56), respectively, indicating statistically significant improvement over the MCID. Conclusion: Successful clinical outcomes can be achieved with full-endoscopic decompression via the interlaminar approach for lumbar central spinal stenosis in patients for the defined indications. Level of Evidence: 2